Forest Evapotranspiration and Energy Flux Partitioning Based on Eddy Covariance Methods in an Arid Desert Region of Northwest China - Xiaohong Ma; Qi Feng; Yonghong Su; Tengfei Yu; Hua Jin (Advances in Meteorology)
In this study, the characteristics of energy flux partitioning and evapotranspiration of P. euphratica forests were examined in the extreme arid region of Northwest China. Energy balance closure of the ecosystem was approximately 72% (H + LE = 0.72 ∗ (Rn-G)+7.72, r2=0.79, n=12095), where Rn is the net radiation, G is the soil heat flux, H is the sensible heat flux, and LE is the latent heat flux. LE was the main term of energy consumption at annual time scale because of higher value in the growing season. The ratios of the latent (LE) and sensible (H) heat fluxes to net radiation were 0.47 and 0.28 throughout the year, respectively. Moreover, the yearly evapotranspiration of P. euphratica forests was 744 mm year−1. And the mean daily ET was 5.09 mm·d−1 in the vibrant growing season. In particular, a small spike in the actual evapotranspiration distribution occurred during the soil ablation period due to the higher temperature and sufficient soil moisture associated with soil thawing. This period is accompanied by a series of physical processes, such as moisture transfer and heat exchange.